2019
DOI: 10.1371/journal.pone.0216256
|View full text |Cite
|
Sign up to set email alerts
|

Altered superoxide dismutase-1 activity and intercellular adhesion molecule 1 (ICAM-1) levels in patients with type 2 diabetes mellitus

Abstract: Inflammation and oxidative stress are linked to type 2 diabetes mellitus (T2DM). In this work, we analyzed patients’ blood markers of antioxidant capacity, oxidative stress and inflammation in individuals with T2DM, in pre-diabetes state (pre-DM) and controls without diabetes. Patients were divided into three groups, according to glycated hemoglobin A1c (HbA1c): <7%, 7–9%, and >9%. Superoxide dismutase (SOD) and glutathione peroxidase (GPX) activities, total thiols, nitric oxide ( • NO),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 42 publications
1
17
0
2
Order By: Relevance
“…Oxidative stress is responsible for mitochondria and sarcoplasmic reticulum structural changes, favoring the increase in cell death in animal models of DM [ 7 ]. A high plasma superoxide dismutase (SOD) level is detected in DM, which is not accompanied by an increase in plasma glutathione peroxidase (GSH-Px), leading to an increase in oxidative stress and consequent uncontrolled lipid peroxidation [ 9 ]. Thus, ROS and malondialdehyde (MDA), a stable end product of lipid peroxidation, are increased in DM, indicating failure of the antioxidant system [ 25 , 26 , 27 ], which can result in damage to the cells ( Figure 1 ).…”
Section: Molecular Mechanisms Involved In Diabetes-induced Cardiac Remodelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress is responsible for mitochondria and sarcoplasmic reticulum structural changes, favoring the increase in cell death in animal models of DM [ 7 ]. A high plasma superoxide dismutase (SOD) level is detected in DM, which is not accompanied by an increase in plasma glutathione peroxidase (GSH-Px), leading to an increase in oxidative stress and consequent uncontrolled lipid peroxidation [ 9 ]. Thus, ROS and malondialdehyde (MDA), a stable end product of lipid peroxidation, are increased in DM, indicating failure of the antioxidant system [ 25 , 26 , 27 ], which can result in damage to the cells ( Figure 1 ).…”
Section: Molecular Mechanisms Involved In Diabetes-induced Cardiac Remodelingmentioning
confidence: 99%
“…DCM includes cell death, changes in energy metabolism and the extracellular matrix, inflammation, oxidative stress, neurohormonal activation and modification in ion transport [ 5 ]. DM [ 6 , 7 , 8 , 9 , 10 , 11 ] can induce cardiac changes due to remodeling and culminate in cardiac dysfunction, which is independent of other cardiac comorbidities, such as coronary artery disease, hypertension and valvular heart disease [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In other studies reported, reduction in antioxidant enzymes and oxidative stress was associated with protein glycation ( Dzięgielewska-Gęsiak et al, 2019 , Ghelani et al, 2018 ). Protein glycation was reported to cause the inactivation of antioxidant enzymes due to the alteration of amino acids present in the active sites of these antioxidant enzymes ( Tavares et al, 2019 ). This phenomenon decreases the activity of CAT and SOD; it also contributes to the further elevation of oxidative stress ( Tavares et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In one correlation study comparing SOD activity in the HbA1c group (<7, 7–9, and >9), the SOD activity was higher in the DM patient compared to the normal. DM group with HbA1c < 7 had a higher significant SOD activity compared to the other groups [ 23 ]. Nonetheless, Doddigarla et al [ 24 ] reported a contrary result where the patient with T2DM presented with low SOD activity and there was a correlation between decreased SOD activity and increased glycemic index.…”
Section: Discussionmentioning
confidence: 99%